PENINGKATAN KETRAMPILAN KADER DALAM SISTEM LIMA MEJA DI POSYANDU TERATAI XII KECAMATAN GEMOLONG KABUPATEN SRAGEN - Igiany, Prita Devy; Asriati, Yul (Poltekkes Kemenkes Riau, 2022)
Health cadres are a manifestation of the active participation of the community in posyandu. Cadres are the right target in implementing health programs because they are considered to be the first referral place for health services so that health cadres around the community are required to have a level of knowledge so that they can carry out the functions of the five tables properly. Cadres at Posyandu Teratai XII do not know and understand the five table system well, so the implementation of the posyandu is not optimal. The socialization and training of the five table system for Posyandu Teratai XII cadres are deemed necessary to increase the knowledge and competence of cadres in providing services to the community at the posyandu. The method used in this activity was to organize material debriefing and discussions by the community service team and assisting the implementation of the posyandu. Based on the pretest and post-test conducted on posyandu cadres, it showed that the cadres' level of knowledge about the five-table system had increased by 50%, the initial knowledge of 41.43% became 91.43%. In addition, based on the evaluation of posyandu activities, posyandu services have increased with the functioning of the five table system at Posyandu Teratai XII. This increase shows that the material provisioning activities and the five table system training, as well as mentoring, are running effectively.